Lasiodiplodia theobromae-induced alteration in ROS metabolism and its relation to gummosis development in Prunus persica - Zhang, He (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.